Sự hoài nghi tuyên bố tốt cho sức khỏe ở người tiêu dùng trong ngành thực phẩm: Các tiền tố và hệ quả - Nguyễn Hoàng , Sinh; Luân Phúc , Cường; Phùng Quốc , Thăng (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2021)
Health claims play an important role in connecting consumers and manufacturers. However, because of health claims’ credence attributes, consumers tend to treat them with a certain level of skepticism. This study aims at determining and examining antecedents to consumers’ skepticism towards health claims and consequences of such attitudes in the food industry. An online survey was conducted to gather 512 responses from Vietnamese consumers. Structural Equation Modeling (SEM) was used to test theoretical models and hypotheses. The results indicate that consumers’ skepticism toward health claims is affected by four antecedents. In which, two personality traits are cynicism and negative self-esteem; two situational factors are food safety awareness and marketplace knowledge. In contrast to prior research, marketplace knowledge is found to have a negative impact on consumers’ skepticism. The results also show that the effects of positive self-esteem are negligible. Besides, relationships between skepticism and its consequences are found.